World Bank Research Digest, Vol. 6(2) - World Bank (Washington, DC, 2014)
In this issue: demystifying the Chinese economy; power tariffs in Africa: caught between cost recovery and affordability; has the global banking system become more fragile? How caste and gender affect schooling in rural Pakistan; surviving the global financial crisis: the role of foreign ownership; how do labor market institutions affect shadow economies in Europe? And innovation for green growth.